Avaliação das alterações cognitivas, saúde mental e qualidade de vida em pacientes adultos com distúrbio respiratório obstrutivo do sono de grau leve - Klichouvicz, Priscila Calixto [UNIFESP] (2020)
Introduction: Sleep Disordered Breathing (SDB) can lead to cognitive impairments, mood and can reduce patient´s quality of life. There are different cognitive domains, such as intelligence, memory, attention, language, executive functions, among others. Estimate that cognitive impairment is caused by serious disorders, however, the magnitude of these impairments is not very likely, especially in the mild forms, including Upper Airway Resistance Syndrome (UARS) and Mild Obstructive Sleep Apnea (OSA). Objective: This study aimed to evaluate the cognitive functions, mental health and quality of life in patients with mild SDB. Methods: 52 participants with either genders and with body mass index (BMI) < 35 Kg/m2 were included; between the ages of 25 to 50 years, according to clinical polysomnographic diagnosis of UARS (AHI score < 5 events/hours and RDI score ≥ 5 events/hour with excessive daytime sleepiness (EDS) complaints and Epworth Sleepiness Scale scores (ESS) > 10 and/or the Modified Fatigue Impact Scale scores ≥ 38); Mild OSA (5 events/hour ≤ AHI < 15 events/hour with complains) and control group without diagnosis of Sleep Breathing Disorders and no complains. Participants were allocated into 2 groups: Group 1 – Control group (n = 19) and Group 2 – UARS + mild OSA or mild SDB (n = 33). The evaluations consisted of full-night polysomnography exam (PSG); Epworth Sleepiness Scale (ESS); Pittsburgh Sleep Quality Index (PSQI); Modified Fatigue Impact Scale (MFIS-BR); Functional Outcomes of Sleep Questionnaire (FOSQ); application of cognitive instruments to assess memory, attention, executive functions; application of Beck Depression Inventory; Beck Anxiety Inventory; Lipp`s Stress Symptoms Inventory for Adults (ISSL) and finally anthropometric measurements were also collected. Results: Regarding the sleep structure, it was found that the mild SDB group showed higher proportion of the sleep stage N2 and lower proportion of sleep stage N3 when compared to the control group (p= 0,006, p=0,008, respectively). For the cognitive assessment it was observed that patients with mild Sleep Disordered Breathing had a lower performance in the immediate episodic memory domain (p=0,02) with no significant differences in the other cognitive functions evaluated. The mild SDB group showed an increase in the depressive symptoms and in the fatigue score when compared to control group (p = 0,05, p = 0,007, respectively). Conclusions: Mild SDB may be associated with symptoms of depression, fatigue and changes in sleep structure with reduced slow- wave sleep. Cognitive alteration was observed in the domain of verbal episodic memory, however, in the absence of other changes it may not have relevant clinical significance. Interestingly and contrary to our hypothesis, the UARS group showed more cognitive changes, consistently and significantly when compared to mild OSA group, however UARS and mild OSA group did not differ in relation to symptoms of depression, anxiety, stress, fatigue, impact of sleepiness on quality of life, excessive sleepiness and some sleep parameters.